2015
DOI: 10.1371/journal.pone.0142652
|View full text |Cite
|
Sign up to set email alerts
|

Does Fish Oil Have an Anti-Obesity Effect in Overweight/Obese Adults? A Meta-Analysis of Randomized Controlled Trials

Abstract: ContextAccumulating evidence has suggested favorable effects of fish oil on weight loss in animal experiments; however, findings remain inconsistent in humans.ObjectsThe meta-analysis was performed to investigate the influence of fish oil on some parameters of body composition in overweight/obese adults.DesignHuman randomized, placebo-controlled trials were identified by a systematic search of Embase, PubMed, the Cochrane Library, web of science and reference lists of related reviews and articles. The random-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 70 publications
3
47
0
4
Order By: Relevance
“…; Buckley & Howe, ), a recent meta‐analysis indicated that PUFA supplementation does not promote anti‐obesity effects in overweight/obese individuals, in agreement with our results (Du et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…; Buckley & Howe, ), a recent meta‐analysis indicated that PUFA supplementation does not promote anti‐obesity effects in overweight/obese individuals, in agreement with our results (Du et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…In comparison, the intakes of EPA and DHA in the United States are low for omega 3s ~0.1–0.2 g/d [66] and the current recommendations vary from 1 g/d to 4 g/d [67] with upper levels necessary to reduce hypertriglyceridemia. Higher doses have been used in human studies from 4.2 g/d [68] to doses up to 15 g/d described in a recent meta-analysis [69, 70]. However, in human studies, the effect of fish oil in improving fat oxidation and whole-body metabolism is inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, there are limited trails examining the effects of nutritional approaches for suppressing obesity-related intestine inflammation. This may be due to the fact that it is a relatively new concept that obesity-related intestine inflammation precedes and correlates with insulin resistance (Ding et al 2010; Du, et al 2015). However, it is expected that in the future more trials will specifically address whether and how diets suppress intestine inflammation in the context of preventing or reversing obesity-related metabolic dysregulation.…”
Section: Nutritional Approaches For Suppression Of Obesity-associamentioning
confidence: 99%
“…In overweight or obese children, supplementation of CLA also reduced body fatness (Racine, et al 2010). However, there also are many studies that could not support an exact anti-obesity role for n-3 PUFAs in overweight/obese subjects, which suggest the necessity of conducting more large-scale and long-term clinical trials (Du et al 2015). Compared with PUFAs, MUFAs appear to be more promising in terms of reducing fat mass.…”
Section: Nutritional Approaches For Reducing Fat Depositionmentioning
confidence: 99%